AN EXPERIMENTAL STUDY OF NATURAL CONVECTION IN THE HOTTEST CHANNEL OF TR1GA 2000 kW REACTOR - Umar, E.; Kamajayaz, K.; Suwono, A.; Tandian, N. P.; Hardianto, T. (BATAN, 2005)
AN EXPERIMENTAL STUDY OF NATURAL CONVECTION IN THE HOTTEST CHANNEL OF TRIGA 2000 kW REACTOR. With the increase of radioisotope demand, in 1995, National Nuclear Energy Agency of Indonesia made a decision to upgrade the power of the TRIGA Mark II reactor from 1 MW to 2 MW maximum power. The reactor reached its first criticality on May 13, 2000. To accomplish the safety evaluation of the reactor, a thermal hydraulic analysis was carried out by using thermal hydraulic computer code. This code calculates the natural convection flow through water coolant bounded by vertical cylindrical heat sources. In this paper, it will be reported the experimental study of natural convection in the hottest channel of TRIGA 2000 kW reactor. The purpose of the experimental study is to verify the theoretical analysis, especially the temperature distriburtion in the hottest coolant channel. In this experiment, a special probe for temperature detection has been designed and inserted to central thimble (CT). In the experiment, eight thermocouples were used to measure the bulk temperature of the water at different position in the cooling channel and simultaneous quantitative measurement of the temperature distribution were done by using a data acquisition cards system. The result obtained theoretically using the STAT code has been verified by this experimental study.